The effect of global political risk on stock returns: A cross-sctional and a time-series analysis (2020)
Given the rise of political uncertainty, it is important to develop an understanding of their effect on financial markets. We use a political risk measure to calculate their effect on stock markets based on a political risk measure. The political risk proxy is related to cross-country returns and two portfolios: one with upside and other with downside political risk. Time-series and cross-sectional analysis are conducted to measure the effectiveness of this measure on global markets. The results evidence that an increase in global political risk is negatively correlated with an upside portfolio containing global stock returns.